A cascade reaction for the new and direct synthesis of indolofuroquinoxalines. Issue 28 (1st March 2016) - Nikumbh, Satish P.; Raghunadh, Akula; Rao, T. Srinivasa; Murthy, V. Narayana; Joseph, Suju C.; Murthy, Y. L. N.; Pal, Manojit
Abstract : A cascade reaction has been developed for the direct and one-pot synthesis of 7 H -indolo[3′, 2′:4, 5]furo[2, 3- b ]quinoxaline derivatives. Abstract : The 7 H -indolo[3′, 2′:4, 5]furo[2, 3- b ]quinoxaline derivatives are synthesized directly from methyl 2-(2-chloro-1 H -indol-3-yl)-2-oxoacetate or its N -alkyl derivatives under neutral or mildly acidic conditions. This new one-pot methodology was found to be general and greener as it avoids the use of environmentally harmful POCl3 and strong alkali required for the previously reported method. It is also amenable for scale-up.